2017
DOI: 10.14569/ijacsa.2017.080522
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Method Study for Investigating Critical Success Factors (CSFs) of E-Learning in Saudi Arabian Universities

Abstract: Abstract-ElectronicLearning (E-Learning) in the education system has become the obvious choice of the community over the globe because of its numerous advantages. The main aim of the present study is to identify Critical Success Factors (CSFs) and validate them for successful implementation of the E-Leaning at Saudi Arabian Universities. This study developed a multidimensional instrument for measuring the E-Learning CSFs in the higher educational institutions of Saudi Arabia. The study reviewed various CSFs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…The study found information quality to be the most important variable that influenced the usability of the e-learning system across all attribute categories. The results match those observed in earlier studies that the information quality dimension plays a significant role in e-learning system usability evaluation (Bringula & Basa, 2011;Hasan, 2014;Noorulhasan, Muhammad, Sanober, Rafik, & Shah, 2017;Zaharias & Poylymenakou, 2009). Hasan (2014) found that content was perceived as the most important quality from a students' perspective.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The study found information quality to be the most important variable that influenced the usability of the e-learning system across all attribute categories. The results match those observed in earlier studies that the information quality dimension plays a significant role in e-learning system usability evaluation (Bringula & Basa, 2011;Hasan, 2014;Noorulhasan, Muhammad, Sanober, Rafik, & Shah, 2017;Zaharias & Poylymenakou, 2009). Hasan (2014) found that content was perceived as the most important quality from a students' perspective.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Thuseethan et al (2014) revealed that visual inconsistencies in an e-learning system design resulted in chaos and lack of interaction from the students' perspective. Elsewhere, also in contrast to this study, in the Saudi Arabian context, the e-learning system visual design was found to be a critical success factor for implementation and the use of an e-learning system with user-friendly items being the most significant factor for the successful use of elearning (Noorulhasan et al, 2017). Even though students regarded visual design as the fourth most important category, the differences are marginal compared with learnability and navigation dimensions (17.88, 18.21 and 18.68 respectively).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Previous research has shown that critical success factors (CSFs) play a key role in the successful implementation of e-learning. Besides, it's also been shown that essential factors of different dimensions can have different effects on the e-learning system [5][6][7]. Thus, it is important that the analysis and resource allocation of the E-learning CSFs be speci cally examined and that a proposed framework of the success factors of E-learning is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Online teaching is not just about altering the medium. It is also about course design (Anggrainingsih et al 2018;Noorulhasan et al 2017), technical skill to use learning management system/LMS (El-Gawad and Woollard, 2019), and understanding of how learners learn in an online environment (Alqahtani and Rajkhan, 2020;Bani-Salameh and Fakher, 2015;Martin et al, 2019). Instructors in online learning need to change their roles in teaching from "teacher-centered to student-centered, low-interactor to high-interactor, and low-initiator to highinitiator" (Beck and Ferdig, 2008).…”
Section: Introductionmentioning
confidence: 99%